A Novel Technique for Minimizing the Metal Artifacts on Anterior Teeth in Cone-Beam Computed Tomography - Safi, Yaser; Fazlyab, Mahta; Asgary, Saeed; Fazlalipour, Sahar (Iranian Endodontic Journal, 2019)
In endodontics, metal artifacts are the major weak points of employing cone-beam computed tomography (CBCT) in teeth with metallic posts and restorations. The aim of this article is to introduce a novel technique for preparation of beneficial CBCT images of anterior teeth with metal posts and/or crowns. In this novel technique, the patient who was instructed to take CBCT images for reason of implant surgery, was asked to puff out his cheeks/lips during the rotation of x-ray tube. By comparing the image taken with this technique to normal image it was obvious that after applying the cheek puffing technique, the metal artifacts around restored anterior teeth significantly reduced. Then it seems that this novel technique removes the metal artifacts from the crowned teeth to distances far from the tooth structure and enables more accurate diagnosis. Keywords: Artifact; Cone-Beam Computed Tomography; Cone-Beam Computer-Assisted Tomography; Endodontics; Metal Artifact Reduction